Characteristics of Dioscorea esculenta Starch Exposed to Citric Acid and Autoclaving-Cooling Treatment - Andriana Puspitasari; Yudi Pranoto; Priyanto Triwitono; Dwi Larasatie Nur Fibri (The University of Lampung, 2026)
Starch is an abundant carbohydrate reserve found in plants, such as Dioscorea esculenta. Starch can be a staple food and energy source. However, native starch has limitations, required modification processes. The research investigated effect of citric acid and autoclaving-cooling in several cycles for its starch characterization. Starch was extracted and pretreated with citric acid (0.1 M) for 6 h at a ratio of starch and water of 1:4 (w/v). Starch was then modified by autoclaving-cooling using different cycles (1, 2, 3, 4, and 5). Analyses included recovery yield, proximate composition, amylose content, water or oil holding capacity, solubility, swelling power, and color. The results showed no significant difference in the recovery yield, decreased protein, and increased amylose. Autoclaving-cooling modification in Dioscorea esculenta starch enhances the water holding capacity (WHC), oil holding capacity (OHC), and solubility, while reducing its swelling power. In terms of the color of starch after modification by autoclaving-cooling, there was a decrease in lightness (L*) and the whiteness index (WI) values. The results suggested that starch produced with two cycles of autoclaving-cooling was better, as indicated by an increase in amylose content of 25.14%. These findings are expected to provide alternative sources of functional foods and contribute to the utilization of local food ingredients.